Antibullying Interventions in Schools : Ingredients of Effective Programs - Smith, J. David; Cousins, J. Bradley; Stewart, Rebecca (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
Because bullying is a serious problem in Canadian schools, antibullying programs have been widely implemented to redress the problem. School principals in Ontario (N=395) completed a questionnaire to document the severity of bullying, the amount of anti‐bullying resources, and the variety of antibullying activities in their schools. Results reveal that reductions in bullying in previous years, sufficiency of resources for resolving bullying, and amounts of antibullying programming were all positively associated antibullying program outcomes. These data suggest that the investment of time, effort, and money in school‐based antibullying initiatives can lead to safer and more peaceful schools environments. Key words: bullying, primary prevention, program evaluation Comme l’intimidation est un problème sérieux dans les écoles canadiennes, des programmes de lutte contre l’intimidation font leur apparition un peu partout. Des directeurs et directrices d’école en Ontario (N = 395) ont rempli un questionnaire visant à documenter la gravité du problème, les ressources existantes et les diverses activités anti‐intimidation mises en place dans les écoles. D’après les résultats du questionnaire, la réduction de l’intimidation au cours des années précédentes, la pertinence des ressources en place pour faire face aux incidents d’intimidation et le nombre de programmes de lutte contre l’intimidation étaient tous corrélés à l’amélioration des résultats en la matière. Ces données semblent indiquer que le temps, les efforts et les fonds investis dans les initiatives anti‐intimidation contribuent à créer un climat de paix et rendre les écoles plus sécuritaires. Mots clés : intimidation, prévention, évaluation de programmes.